REVITALISING MORAL EDUCATION IN THE DIGITAL AGE: STRATEGIES FOR CHARACTER BUILDING AMONG GENERATION Z AMIDST THE TIDE OF DISINFORMATION AND THE DECLINE OF ETHICAL SOCIAL MEDIA USE - Miranu Triantoro; Rahmat Shodiqin (Indonesian Journal of Education (INJOE), 2026)
This study aims to analyse the revitalisation of moral education in the digital age as a strategy for character building among Generation Z amidst the tide of disinformation and the erosion of social media ethics. The method employed is a literature review (library research) using a descriptive-analytical qualitative approach. The findings indicate that traditional moral education, which is instructional and abstract in nature, is no longer effective in addressing the complex moral challenges of the digital space; consequently, a paradigm shift is required towards an approach that is contextual, participatory, and grounded in authentic digital experiences. Twelve character-building strategies were identified as a synergistic supporting ecosystem: (1) strengthening critical digital literacy, (2) internalising the values of Pancasila through creative content, (3) digital project-based learning, (4) simulations of digital moral dilemmas, (5) intergenerational digital parenting, (6) transforming schools into value ecosystems, (7) utilising AI for educational interventions, (8) strategic partnerships with social media platforms, (9) authentic assessment based on digital portfolios, (10) social and cultural movements for digital ethics, (11) integration of counselling and mental health services, and (12) national and international collaborative networks. The success of this strategy is not measured solely by a reduction in the statistics of ethical violations, but rather by the emergence of Generation Z possessing moral resilience—the moral fortitude to navigate the digital space critically, ethically, and autonomously. This study concludes that the revitalisation of moral education is an existential imperative to ensure that Indonesia’s digital transformation produces a generation that is not only technologically proficient but also possesses strong character, is critical of manipulation, empathetic, and committed to digital justice as the foundation of 21st-century democracy.